Exploration of the Gaps in the Enactment and Implementation of the Domestic Violence Act of South Africa - Sabelinah M. Tshoane; Paul O. Bello; Jacob T. Mofokeng; Adewale A. Olutola (Khazanah Hukum, 2023)
Domestic violence (DV) by women against men is as rife as violence by men against women. This paper argues that viewing DV as a crime committed only by men against women and never by women against men is wrong. The study explored the existence of domestic abuse against men and the gender neutrality of the Domestic Violence Act of South Africa using a mixed-methods research strategy. The Gauteng, Limpopo, and KwaZulu-Natal provinces in South Africa were used for data collection. A sample size of roughly 200 represents quantitative aspects. Open invitations were also extended to 30 people to participate in semi-structured one-on-one interviews for the qualitative research component, while questionnaires were sent to approximately 170 respondents. Participants and respondents included South African Police Service members who deal with gender-based violence (GBV); the Department of Social Development; the Commission for Gender Equality; non-governmental organisations (NGOs) in three selected provinces that deal with DV against men, namely Aka Sosha, Moshate, Matrix, and Real Men; male survivors of DV; religious leaders; members of the Department of Social Development; houses of traditional leaders; members of Families South Africa (Famsa); social workers; a psychologist; and members of Sonke (a GBV support group). The results revealed that South African men often experience domestic abuse. Secondly, the police do not treat male abuse victims in the same manner as female victims. Thirdly, there are no support services for male victims in South Africa. The study recommends the fair implementation of the law and legal support. Although the Domestic Violence Act of 1998 (as amended) is gender-neutral, its implementation is not. There is a need for healthcare professionals, mental healthcare workers (including psychologists and certified counsellors as community workers), police officials, legal personnel (including court administrators), and religious leaders to receive training on men's issues. This training will aid in providing care, protection, and counselling to male victims of DV.